The Extent To Which The Content Of The Third-Grade Intermediate Mathematics Textbook Conforms To International Standards (Journal of the College of Basic Education, 2026)
The present study aimed to (The extent to which the content of a book matchess for the third intermediate grade in the light of the international quality standards). And determine the problem of the study the following question: The availability of international standards in the content of mathematics textbooks for grades third) average in Iraq? To achieve the goal of the research, the tow researcher using descriptive analytical method approach to the study. And the tow research community of teachers and teachers who are studying mathematics for grade third average in baghdad province and totaling (100) teacher and school. and tow researcher used stratified random sample in it. The two researcher determining global standards for grade third average by comparing goals and wrote mathematics intermediate stage with global standards to determine the criteria for the third stage, to determine the availability of international standards where by directing a questionnaire exploratory to a group of Experts , as well as through access to educational literature, and modern standards, as well as global standards for math standards of the American National Council, (NCTM) and consisted resolution content analysis finalized after making sure of the sincerity of Four areas are (numbers and their operations, algebra and relations and functions, geometry and measurement, and data analysis and statistics and probability) and included (61) Index for the third grade, has been verified by the virtual honesty and truthfulness structural, and calculate the reliability coefficient manner Alvak Ronbach and average reliability coefficient for third grade (0.94) this shows that the resolution on a high degree of stability. Was calculated by Chi-square paragraphs content analysis if they are available any function transferred to a questionnaire Calendar The number of indicators (19) index in the third grade in order to determine the proportion of availability and were calculated center likely and weight percentile and can be seen from the results:that the degree of availability of international standards in the content of math books forthe third stage by a few this indicates that there is a weakness in the content of math books and that some of the criteria did not find her subject is noteworthy.content math books for middle stage did not achieve quality because it did not get a percentage (80%) and above.